Timed to Say Goodbye: Does Unemployment Benefit Eligibility Affect Worker Layoffs? - Andrea Albanese; Corinna Ghirelli; Matteo Picchio (Institute of Labor Economics (IZA), 2019)
We study how unemployment benefit eligibility affects the layoff exit rate by exploiting quasi-experimental variation in eligibility rules in Italy. By using a difference-indifferences estimator, we find an instantaneous increase of about 12% in the layoff probability when unemployment benefit eligibility is attained, which persists for about 16 weeks. These findings are robust to different identifying assumptions and are mostly driven by jobs started after the onset of the Great Recession, in the South and for small firms. We argue that the moral hazard from the employer's side is the main force driving these layoffs.
Keywords: C31; C41; J21; J63; J65; 330; unemployment insurance; layoffs; employer-employee moral hazard; difference-in-differences; heterogeneous effects